National Income Taxation and the Geographic Distribution of Population - Hildegunn Stokke; Jørn Rattsø (European Regional Science Association (ERSA), 2015)
Income taxation may affect the regional allocation of population when prices vary over space. Our contribution is to compare different income tax systems in a migration equilibrium model for Norway using improved measure of regional wage differences. We apply register data of individual wages for the entire population to identify wage differences, while controlling for both observable and unobservable worker characteristics and allowing for dynamic learning effects on wages. We estimate regional differences in cost of living based on detailed data on housing prices. The model is calibrated to the current nominal income tax system and compared to an undistorted equilibrium without income tax. We investigate two alternative tax systems: Real income taxation where the real tax burden is proportional to real wages and equal real taxes across regions motivated by taxation of amenities. The numerical simulations document large shifts in the regional distribution of the population as the result of income taxation. The elasticity of population with respect to tax payments comes out with a value of -2.64. Nominal income taxation creates a disincentive to locate in productive high-wage regions, and generates a deadweight loss due to locational inefficiencies equal to 0.028% of income. Real income taxation gives a geographic distribution of the population closer to the undistorted equilibrium, and hence with lower deadweight loss, while equal real taxes is the least efficient tax system.
Keywords: H24; H77; J61; R23; 330; Income taxation; regional taxation; cost of living; amenities